CORRELATION OF HBA1C LEVEL WITH DIABETIC RETINOPATHY - Talat, Kainaat; Shahid Hamid Mahmud,; Muhammad Fahad Ikram,; Shehar Bano,; Tariq Munawar,; Abdul Rafe, (Journal of Ayub Medical College Abbottabad, 2025)
Background: Diabetes mellitus (DM) is considered to be a significant universal public health issue. According to the American Society of Retina Specialists, diabetic retinopathy (DR) is a complication of diabetes that damages retinal blood vessels. A Japanese study showed that HbA1C values can be considered as predictors for the development of DR. Thus, this study aimed to determine the correlation between HbA1c level and Diabetic Retinopathy. Methods: A descriptive cross-sectional study was conducted at the Department of Ophthalmology, Combined Military Hospital Kharian, from February 2024 to July 2024. Patients of either gender between 40 to 80 years of age with type 2 diabetes mellitus were included in this study. Complete ophthalmic examination was carried out of each patient. HbA1c was measured by standardized assay using high performance liquid chromatography. The data was analyzed using Statistical Package for Social Sciences (SPSS) version 26. Results: Out of 246 patients, 42.7% were male and 57.3% female, with a mean age of 49.26±11.47 years and a mean HbA1c of 9.11±2.54. The overall prevalence of diabetic retinopathy (DR) was 57.7%, with 52.8% having NPDR and 49% PDR. DR prevalence increased with diabetes duration and was significantly higher in those with HbA1c levels between 7–9.9%(p=0.000). The logistic regression identified age, duration of diabetes, and HbA1c levels as critical factors associated with the risk of DR. The odds ratio for HbA1c indicates higher levels are associated with increased DR risk (p<0.005). Conclusion: This study concluded that duration of diabetes and HbA1c level are important risk factors for onset or progression of Diabetic retinopathy in type 2 Diabetes and the patients with poor glycaemic control had severe diabetic retinopathy as compared to the patients with good diabetic control. There is a direct relation between HbA1c level and the severity of diabetic retinopathy.